Nanoporous Carbon-Supported Bimetallic (Ni, Cu, and Fe)-Mo Catalysts for Partial Hydrogenation of Biodiesel - Dolrudee Jaruwat; Napat Kaewtrakulchai; Siwat Siriorarnroj; Atthapon Srifa; Worapon Kiatkittipong; Sumittra Charojrochkul; Masayoshi Fuji; Apiluck Eiad-Ua; Suttichai Assabumrungrat (My University, 2024)
Upgrading biodiesel or hydrogenated fatty acid methyl esters (H-FAMEs) by partial hydrogenation is a second-generation biofuel with high specific fuel characteristics, such as superior cold flow properties, higher oxidative stability, and lower hazardous gas emissions, allowing this biofuel to provide excellent fuel properties, over conventional biodiesel. This study assessed the potential of using nanoporous carbon produced from cattail leaves (CL) as an alternative catalyst support. We synthesized various catalysts including monometallic Mo/NPC, Ni/NPC, Ce/NPC, and Fe/NPC catalysts, as well as bimetallic molybdenum-based catalysts doped with nickel, copper, or iron for the partial hydrogenation of soybean biodiesel. The NPC support demonstrated a surface area (
Keywords: Bimetallic strip; Nanoporous; Carbon fibers; Catalysis and Hydrodesulfurization Studies